Atlas of procedures in neonatology - MacDonald, Mhairi G.; Rais-Bahrami, Khodayar; Ramasethu, Jayashree (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2013)
"The Atlas of Procedures in Neonatology, Fifth Edition, provides detailed, step-by-step instructions on procedures performed in the neonatal intensive care nursery. In an easy-to-follow outline format, with more than 450 drawings and clinical photographs, the book presents clear, current information on indications, preparation, technique, precautions, and how to avoid potential complications.New for this edition: New chapters covering: Brain and Whole Body Cooling; Bubble CPAP; Educational Principles of Simulation Based Procedure Training to help you stay updated on the latest technology and information Access to free online companion website that includes fully searchable text, image bank and videos so you can access the content anytime, anywhere Video collection has been expanded to include: lumbar puncture, intraosseous infusion, bubble CPAP and pericardiocentesis for both commonly performed procedures and vital emergency procedures"--Provided by publisher.